Investigating the Impact of Green Banking Disclosure, Profitability, Company Size, and Non-Performing Loans on Company Value - Asilah Eka Putri (E-Jurnal Akuntansi, 2024)
Green banking practices encompass not only sustainability but also the potential financial benefits. However, in the short term, issuing green financial products requires substantial capital, which can negatively impact company value. This study aims to analyze the influence of Green Banking Disclosure, Profitability, Bank Size, and Non-Performing Loans (NPL) on Company Value, both individually and collectively. The research sample consists of 8 conventional banks that published sustainability reports on the Indonesia Stock Exchange (IDX) from 2015 to 2022. The analysis results indicate that green banking disclosure and bank size do not significantly affect company value. Conversely, profitability shows a significant positive influence, while non-performing loans exhibit a significant negative impact on company value. Based on these findings, it is crucial for policymakers to innovate and create more contributive green financial products, enhancing their ability to boost bank performance. Additionally, a comprehensive management approach covering all financial aspects is necessary to support the effectiveness of green banking practices.